POTRET HUBUNGAN NASABAH BANK SYARIAH: STUDI DEMOGRAFI WILAYAH PEKALONGAN - Nasrullah, Muhammad; Ismanto, Kuat; Nalim, Nalim (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2017)
This purposes of study is to explore the demography characteristic and relationship of Islamic bank’s customers at Pekalongan residence, by collecting data from a sample of six customers’ Islamic bank. A comprehensive descriptive analysis is used to explain the findings of this study. The result show that: first, most of the customers are moeslem. Second, there is no significant difference amount between men and women customers. Third, most of Islamic banking’s customers are highly educated and have various occupations such as enterpreneurs, employees, and civil government employees. Fourth, most of customers have durable relationship with the banks in less five years and most of them only have maximum Rp 20 millions in their accounts. And they also have relationship with conventional banks. Considering this condition, Islamic banking must improve their corporal efficiency and core banking to increase their competitive advantages.